Authenticity and Psychological Safety: Building and Encouraging Talent Among Underrepresented Students in STEM (Teaching and Learning Inquiry, 2022)
The Undergraduate Scholarships with Mathematics and Science Training, Exploration, and Research Program (US MASTER) is a STEM scholarship program funded by the United States National Science Foundation. It was implemented at an upper-Midwest institution to target and provide structured support to low-income, academically talented undergraduates in biology, chemistry, geography and geographic information science (GISc), environmental sciences, and physics and astrophysics. In addition to providing financial support, the program features an integrated approach to mentorship and advising consisting of an ongoing seminar course in which students engage in collaborative projects, research experiences with a faculty mentor, and targeted academic advising. As part of our assessment efforts, we interviewed student participants regarding their experiences. A consistent theme emerged regarding mentorship: in addition to providing access to professional socialization experiences and the facilitation of competency and performance, students reported that it was the ability to form close relationships based on personal authenticity and feelings of psychological safety and trust that provided the best scaffolding for success in a challenging STEM environment.